High-quality Early Childhood Teaching: Review of Specialized Research - Rodríguez-Carrillo, Julia; Mérida-Serrano, Rosario; González Alfaya, Mª Elena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Relatively little research has been conducted on either the knowledge, skills, and attitudes needed to educate effectively in the early years, or the factors that influence acquisition of a high-quality professional identity among Early Childhood (EC) teachers. By synthesizing recent specialized research this integrative review has found that (1) high-quality EC teachers attend to diversity among children, (2) communities of practice contribute to acquisition of a high-quality EC teaching identity, and (3) weaknesses in Teacher Education programs and contextual factors hinder EC teachers’ high-quality performance. This study concludes by discussing practical implications and directions for future research.